Mechanism of Complement Activation and Its Role in the Inflammatory Response After Thoracoabdominal Aortic Aneurysm Repair - Fiane, Arnt E.; Videm, Vibeke; Lingaas, Per S.; Heggelund, Lars; Nielsen, Erik W.; Geiran, Odd R.; Fung, Michael; Mollnes, Tom E. (Circulation (New York, N.Y.), 2003)
Background— Complement activation contributes to ischemia-reperfusion injury. Patients undergoing thoracoabdominal aortic aneurysm (TAAA) repair suffer extensive ischemia-reperfusion and considerable systemic inflammation. Methods and Results— The degree and mechanism of complement activation and its role in inflammation were investigated in 19 patients undergoing TAAA repair. Patients undergoing open infrarenal aortic surgery (n=5) or endovascular descending aortic aneurysm repair (n=6) served as control subjects. Substantial complement activation was seen in TAAA patients but not in controls. C1rs-C1-inhibitor complexes increased moderately, whereas C4bc, C3bBbP, C3bc, and the terminal SC5b-9 complex (TCC) increased markedly after reperfusion, reaching a maximum 8 hours after reperfusion. Interleukin (IL)-1β, tumor necrosis factor α (TNF-α), and IL-8 increased significantly in TAAA patients but not in controls, peaking at 24 hours postoperatively and correlating closely with the degree of complement activation. IL-6 and IL-10 increased to a maximum 8 hours after reperfusion in the TAAA patients, were not correlated with complement activation, and increased moderately in the control subjects. Myeloperoxidase and lactoferrin increased markedly before reperfusion in all groups, whereas sICAM-1, sP-selectin, and sE-selectin were unchanged. No increase was observed in complement activation products, IL-1β, TNF-α, or IL-8 in a mannose-binding lectin (MBL)–deficient TAAA patient, whereas IL-6, IL-10, myeloperoxidase, and lactoferrin increased as in the controls. Two other MBL-deficient TAAA patients receiving plasma attained significant MBL levels and showed complement and cytokine patterns identical to the MBL-sufficient TAAA patients. Conclusions— The data suggest that complement activation during TAAA repair is MBL mediated, amplified through the alternative pathway, and responsible in part for the inflammatory response.